The influence of collective bargaining on large police agency salaries: 1990–2000 - Wilson, Steve (American journal of criminal justice, 2006)
Collective bargaining between police management and unions is an important process that determines many aspects of police work, particularly the monetary benefits for line officers like salary and fringe benefits. Working with limited budgets, police administrators who engage in collective bargaining are obligated to negotiate with union representatives over wage benefits while attempting to maintain adequate financial resources toward other police operations. Though students of policing learn that police unions try very hard to increase economic reward for their members there is limited research on the effectiveness of their efforts. Since economic benefits are the primary focus of police unions, it is important; therefore, to evaluate the impact that collective bargaining has on salaries earned by police personnel. This study examines this issue by combining four waves of the Law Enforcement Management and Administration Statistics for the period 1990–2000. Pooled time series analyses reveal that large organizations that engaged in collective bargaining had higher minimum wages for officers during the period. As predicted, collective bargaining did not affect minimum chief’s salaries.